HUBUNGAN TINGKAT PENGETAHUAN IBU DENGAN GEJALA KARIES GIGI PADA ANAK USIA PRA SEKOLAH - Deshinta Zahra Putri; Ari Damayanti W; Yuniar Angelia P (LPPMK STIKES Widyagama Husada, 2022)
Background : Dental health problems are a very important concern in health development, one of which is caused by the vulnerability of children from dental health disorders. Dental health problems, especially carious teeth, are often complained of by children and adults, dental caries problems cannot be allowed to become severe because it will affect their quality of life, they will experience pain, discomfort, acute and chronic infections, and eating and sleeping disorders. Research Purposes : To determine the relationship between the mother's level of knowledge about dental care and symptoms of dental caries in pre-school children aged 3-6 years in the village of Kedungdalem, Probolinggo. Research Methods : This type of research uses a case control research design. The population in this study were mothers and children aged 3-6 years in the village of Kedungdalem, Probolinggo. The sampling method used a total sampling technique with 55 respondents each one mother and child. Research Result : Mother's knowledge about dental care in Kedungdalem village, Probolinggo, mostly has a good level of knowledge. Some pre-school children aged 3-6 years in the village of Kedungdalem Probolinggo experience symptoms of media dental caries. Conclusion : The level of knowledge of mothers about dental care mostly had a good level of knowledge as many as 48 respondents, the number of children with symptoms of dental caries mostly experienced symptoms of media dental caries as many as 23 children, there was a relationship between the level of mother's knowledge and symptoms of dental caries in pre-school age children 3-6 years in Kedungdalem Village, Probolinggo.